Sildenafil citrate and uteroplacental perfusion in fetal growth restriction - Singh, Priya; Saiyda, Hena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Severe early-onset fetal growth restriction can lead to a range of adverse outcomes including fetal or neonatal death, neurodisability, and lifelong risks to the health of the affected child. Sildenafil, a phosphodiesterase type 5 inhibitor, potentiates the actions of nitric oxide, which leads to vasodilatation of the uterine vessels and might improve fetal growth in utero. The objective is to evaluate effectiveness and safety of Sildenafil citrate for treatment of Doppler velocimetry of uterine, umbilical artery for systolic/diastolic ratio (S/D ratio) at first visit, after 2 hours and then after 12 weeks of treatment. Methods: A case control study was carried out in 96 antenatal women with fetal growth restriction over a period of twelve months. A written informed consent was obtained. Out of 96, 12 were lost to follow up. Of remaining 84 women, 42 were included in the study group and 42 in the control group. First group (case) received Sildenafil citrate 50 mg stat followed by colour Doppler after 2 hours and then 25 mg three times a day for 12 weeks. The second group (control) received placebo in for 12 weeks. Results: Sildenafil treatment was associated with a significant increase in length of pregnancy (P> 0.05) overall mean S/D ratio pre-sildenafil was 5.34±0.93 which reduced to 5.18 ± 0.95 after 2 hours of sildenafil administration and this significant was highly significant (p<0.0001).and also the mean S/D ratio pre-treatment was 6.72±0.38 which decreased to 3.52±0.47 after 12 weeks of sildenafil administration. The difference between them was found to be extremely significant (p<0.0001). Conclusions: Sildenafil citrate can improve utero-placental perfusion and length of pregnancy in pregnancies complicated by IUGR. It appears to have a significantly positive effect on fetal weight. Sildenafil treatment may offer a new opportunity to improve perinatal outcomes, for pregnancies complicated by IUGR. However, these observations require further studies on wide scale.